Variability Analysis of Multiport Systems Via Polynomial-Chaos Expansion - Spina, D.; Ferranti, F.; Dhaene, T.; Knockaert, L.; Antonini, G.; Vande Ginste, Dries (IEEE transactions on microwave theory and techniques, 2012)
We present a novel technique to perform variability analysis of multiport systems. The versatility of the proposed technique makes it suitable for the analysis of different types of modern electrical systems (e.g., interconnections, filters, connectors). The proposed method, based on the calculation of a set of univariate macromodels and on the use of the polynomial chaos expansion, produces a macromodel of the transfer function of the multiport system including its statistical properties. The accuracy and the significant speed up with respect to the classical Monte Carlo analysis are verified by means of two numerical examples.